Dual ectopic thyroid associated with thyroid hemiagenesis. (27th April 2018) - Nakamura, Shigenori; Masuda, Teruyuki; Ishimori, Masatoshi
Summary: We report a case of a 15-year-old girl with a midline neck mass that was first noted 2 or 3 years previously. She had been treated with levothyroxine (L-T4) for congenital hypothyroidism until 11 years of age. Ultrasonography revealed an atrophic right thyroid (1.0 × 1.6 × 2.6 cm in size) and a mass (2.3 × 1.0 × 3.5 cm in size) in the upper part of the neck. No left lobe of the thyroid was detected. On further evaluation, Tc-99m pertechnetate thyroid scintigraphy and CT showed ectopic thyroid tissue in the lingual region and infrahyoid region. Thus, she was diagnosed as having dual ectopic thyroid and thyroid hemiagenesis. The atrophic right thyroid was thought be non-functional. Treatment with L-T4 was started to reduce the size of the dual ectopic thyroid tissue. This may be the first reported case of dual ectopic thyroid associated with hemiagenesis detected only by ultrasonography. Learning points: Ultrasonography can confirm the presence or absence of orthotopic thyroid tissue in patients with ectopic thyroid. The cause of congenital hypothyroidism should be examined. Clinical manifestation of ectopic thyroid may appear when the treatment with L-T4 is discontinued. Annual follow-up is needed in all children when their thyroid hormone replacement is stopped.